Structure Design and Kinematics Simulation of a Novel 7-DOF Upper Limb Rehabilitation Exoskeleton Robot - Tongtong Zhao; Yue Zhang; Gangsheng Cao; Chunming Xia (Jixie chuandong)
Aiming at the existing problems of rehabilitation robots in passive rehabilitation training for patients with severe upper limb hemiplegia， a novel 7-DOF upper limb exoskeleton robot is proposed， and a new hand fixator is designed to replace the grip of the traditional exoskeleton to better achieve the effective wrist training for patients with severe upper limb hemiplegia. According to the exoskeleton model， the Denavit-Hartenberg （D-H） coordinate system is established by using Matlab， and the workspace is simulated to verify that the workspace met the design requirements. Dynamics simulation of exoskeleton is performed by using Adams. In view of the problem that the simulation results do not conform to the reality due to the lack of the injured limb in simulation， a new design that adds the weight of the patient's upper limb to the center of mass of the exoskeleton is adopted. According to the analysis of the loading characteristics， the rationality of the selection of the robot driver is verified， which provides a theoretical basis for the development of the physical prototype.